Design and Position Analysis of a 2T1R Parallel Mechanism with Bending Translation Characteristics - Gao Bo; Shi Zhixin (Jixie chuandong)
Based on the topological design theory and the method of the parallel mechanism of position and orientation characteristic (POC) theory. A two-translation one-rotation (2T1R) parallel mechanism with symbolic position forward solution and partial motion decoupling characteristics was proposed. The topological performance of the mechanism was analyzed, including orientation features, degrees of freedom, and coupling. Based on the kinematic modeling principle of the topological structure, the analytical position forward solution and analytical inverse solution of the mechanism were solved and verified through the position inverse solution. It has been proven that the mechanism has the motion characteristics of bending and translation. The traditional 2T1R parallel mechanism with only straight motion needs to fit multiple straight movements through algorithms for curve translation. This mechanism can be achieved through only one-dimensional translation, greatly simplifying the complexity of the mechanism and the difficulty of the control algorithm.